As interações no diário de aprendizagem do Curso de Letras da UFPB Virtual: uma leitura interacionista sociodiscursiva - Vitorino, Miqueias dos Santos (2012)
Apprenticeship journals have conquered spaces at the educational activities. In the college courses, theses journals are considered as activity instruments used by teachers and students for reflection, discussion and negotiation of the teaching-learning process. It is not different at the education through web context. In this background, journals are reinterpreted by the agents of the educational activity with different characteristics. There are many realities in the web-educational activity whose reveal the complexity of the texts produced at that virtual space. This dissertation, whose nature can be considered qualitative-interpretative, has been worried with the following question: how the use of apprenticeship journals by agents of an online educational activity can be characterized? We propose as objectives to answer this question and also verify which discursive spheres and figures of action are mobilized in the textual infrastructure and what this all this info can reveal about the online educational activity.It was possible analyze the infrastructural text elements, as context of textual productions,text themes, facts of action and types of discourse and interpret how educational activity works. Then, we observed how and why the agents write at this space and how and why they keep the interaction online. This study is related to GELIT s researches and has as scope this emergent digital genre, considered as an activity instrument and a space for interaction among teachers, tutors and students. The main theoretical support of this study is the Socio-discursive Interactionism (ISD), represented by Bronckart (2006, 2008, 2009), Machado (1998, 2007, 2009) and others. From the texts, which were co-produced by teachers, tutors and students, we analyzed some characteristics linguistically marked of the educational activity, based on the Ergonomics of Activity, represented by Amigues (2004) and Faïta (2002) studies. Our corpus is constituted by four journals, two of them belong to the course of Semantics of Portuguese Language and the two others belong to the course of Didactics of Portuguese Language. Both courses belong to the program of the Curso de Letras of the UFPB Virtual. The analyzed journals revealed the existence of different profiles of the genre, depending on the types of discourse and on the text themes founded: the chronicle journal, inwhich is present the narrative of personal experiences (in)directly (or not) related to the student apprenticeship on the course; the abstract journal, whose text themes are related to the course subjects and uses a theoretical discourse to consolidate the text; the dialogued journal is already acknowledged in the educational scenario by scholars and it is characterized as a interactive text with diversified text themes. Towards the research s results, our contribution keeps the discussion about journal s use opened, as instrument of the educational activity, to discuss the necessity and importance of holding a student particular space to interact with the teacher through writing.